About the Magnetic Field of the Earth and that of the Moon as a Gravitational Effect - Lugo, Leandro Meléndez (European Journal of Applied Sciences, 2024)
The magnetic field is a concept in science that often lacks clarity and understanding. It's crucial to emphasize the significance of the magnetic field, particularly for human life. Life as we know it on Earth would not be possible without the existence of the magnetic field. This discussion aims to clarify the sources of the magnetic field in general. By considering the genesis of the field itself, we can explain not only the magnetic field of the Moon but also that of other bodies in the Solar System, such as Earth. The Dynamo Theory, traditionally used to explain the magnetic field of Solar System bodies, is somewhat complex and leaves much to be desired. This work proposes a plausible alternative: a phenomenological theory related to the force of gravity. This theory provides an explanation for the magnetic field of numerous Solar System bodies, particularly Earth, and addresses the absence of a magnetic field on the Moon. Throughout the development of this theory, it is highlighted, among other things, that tides significantly contribute to the magnetic field of both orbiting bodies and the bodies they orbit. As will be demonstrated, the electric dipole effect existing in common matter plays a crucial role in the genesis of the magnetic field. Surprisingly, this effect is closely related to the force of gravity. In conclusion, a fundamental point is presented regarding this electrical bipolarity, intending to ultimately explain the authentic genesis of the force of gravity.